2017
DOI: 10.1055/s-0037-1598111
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Epileptic Spasms as Reflex Seizures Induced by Eating: A Case Report and Literature Review

Abstract: Eating epilepsy (EE) is a rare form of reflex epilepsy in which seizures are induced by eating. It is known that most patients with eating seizures, in fact, suffer from symptomatic temporal lobe epilepsy (TLE), whereas only a few patients with epileptic spasms induced by eating (E-ES) have been reported. The patient was an 8-year-old girl whose magnetic resonance imaging (MRI) of the head detected dysgenesis of the corpus callosum, cerebellar hypogenesis, marked cerebral asymmetry, broad polymicrogyria, periv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…To our knowledge, this is the first case of eating induced multiple generalized seizure types including epileptic spasm, atypical absence with or without myoclonic jerks. It is generally considered that eating triggered seizures are usually related to symptomatic focal epilepsy [1,2,4].The majority of previous studies reported that the most common seizure type induced by eating is focal seizures, and almost occur in symptomatic focal epilepsy [5,6]. Based on our knowledge, this is the first case about the generalized epilepsy with eating-induced seizures, and eight years follow-up of our patient also indicates that generalized epilepsy progressed with age.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To our knowledge, this is the first case of eating induced multiple generalized seizure types including epileptic spasm, atypical absence with or without myoclonic jerks. It is generally considered that eating triggered seizures are usually related to symptomatic focal epilepsy [1,2,4].The majority of previous studies reported that the most common seizure type induced by eating is focal seizures, and almost occur in symptomatic focal epilepsy [5,6]. Based on our knowledge, this is the first case about the generalized epilepsy with eating-induced seizures, and eight years follow-up of our patient also indicates that generalized epilepsy progressed with age.…”
Section: Discussionsupporting
confidence: 60%
“…Eating epilepsy is a kind of rare reflex epilepsy, characterized by seizures closely related to eating [1]. Sei-zures induced by eating are typically focal seizures related to different underlying etiologies [2][3][4]. However, eating-induced multiple generalized seizures have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…An incidence of 1:1000 to 1:2000 of seizures induced by eating is reported in all epileptic patients [8,29]. Eating-induced seizures may be symptomatic or genetic and of variable semiology [30].…”
Section: Discussionmentioning
confidence: 99%
“…28 In a single case report, in which late onset epileptic spasms have been described, topiramate was beneficial. 19 Recent studies confirmed that structural epilepsies or coexistent unprovoked seizures other than ES are poor prognostic factors for pharmacological outcome. 17 Surgical treatment of epilepsy could be a good option for patients with temporal lobe epilepsy and mesial temporal sclerosis with ES.…”
Section: Treatmentmentioning
confidence: 96%
“…27 Several antiepileptic drugs have been used for EE depending on the age of onset and the underlying etiology. 8,17,19,24,25 Use of sodium channel blockers in patients with mesial temporal sclerosis and valproic acid or lamotrigine in patients with negative MRI has been described. 12,17 Clobazam intake before meals was shown to be effective to prevent some cases of eatingprovoked seizures.…”
Section: Treatmentmentioning
confidence: 99%